Reconstitution of protein transport from the endoplasmic reticulum to the Golgi complex in yeast: the acceptor Golgi compartment is defective in the sec23 mutant (The Rockefeller University Press, 1988)
Using either permeabilized cells or microsomes we have reconstituted the early events of the yeast secretory pathway in vitro. In the first stage of the reaction approximately 50-70% of the prepro-alpha-factor, synthesized in a yeast translation lysate, is translocated into the endoplasmic reticulum (ER) of permeabilized yeast cells or directly into yeast microsomes. In the second stage of the reaction 48-66% of the ER form of alpha-factor (26,000 D) is then converted to the high molecular weight Golgi form in the presence of ATP, soluble factors and an acceptor membrane fraction; GTP gamma S inhibits this transport reaction. Donor, acceptor, and soluble fractions can be separated in this assay. This has enabled us to determine the defective fraction in sec23, a secretory mutant that blocks ER to Golgi transport in vivo. When fractions were prepared from mutant cells grown at the permissive or restrictive temperature and then assayed in vitro, the acceptor Golgi fraction was found to be defective.